Impact of Remote Work Environment on Employees’ Job Satisfaction: A Study of BPO Companies in Nepal - Madan Kandel (Pravaha, 2023)
The transition from traditional office environments to remote work settings has been accelerated by technological advancements and the COVID-19 pandemic. This shift, particularly impactful in Nepal's growing Business Process Outsourcing (BPO) sector, has necessitated a re-evaluation of employee satisfaction within virtual workspaces. This study explores the effects of remote work on job satisfaction among employees in Nepal's BPO industry, focusing on factors such as work-life balance, communication effectiveness, technological integration, and overall job satisfaction. Utilizing a descriptive research design, the study employed a structured questionnaire distributed to 407 remote BPO employees. Data analysis through SPSS and Excel revealed that collaboration and relationship building, communication, and monitoring and trust significantly impact job satisfaction, with work-life balance and technology playing more moderate roles. The findings highlight the importance of fostering effective communication, team cohesion, and trust to enhance job satisfaction in remote work environments. The study identifies a gap in existing research concerning Nepal’s specific context and suggests further exploration into how local socio-economic and technological factors influence remote work experiences.